Comparative industrial evolution and the quest for an evolutionary theory of market dynamics - Guido Buenstorf (Max Planck Institute of Economics, 2006)
The paper makes the case for an empirically grounded, bottom-up approach to theory building in evolutionary industrial economics. This approach is based on studying systematically selected industries that are comparable in key dimensions. It opens up opportunities for testing the relevance, preconditions, and generality of explanatory factors in industry evolution. An illustration of the approach is subsequently given by presenting some findings on the evolution of the historical U.S. farm tractor industry.
Keywords: 330